Biosorption of Cr(VI) from Aqueous Solution Using Murraya koenigii (Curry tree) Stems - Suresh, Selvaraj (Orbital: The Electronic Journal of Chemistry, 2016)
In the present work, the sorption capacity of Murraya Koenigii Stems (MKST), an agricultural waste, is identified for the removal of Cr(VI) from aqueous solution and the effect of different process parameters likes pH and adsorbent dosage were studied. pH 1 is observed to be the optimum pH for Cr(VI) sorption onto the biosorbent. The equilibrium data of Cr(VI) sorption fit well with the Langmuir model with a monolayer sorption capacity of 12.25 mg/g. The results show that the metal ion interacts strongly with the biosorbent and can be effectively used in the removal of Cr(VI) from aqueous solution. DOI: http://dx.doi.org/10.17807/orbital.v0i0.867